A Case of Lung Carcinoma with Rhabdoid Phenotype Mimicking an Aspergilloma in Patient with Recurrent Hemoptysis - Kim, Moo Woong (The Korean Academy of Tuberculosis and Respiratory Diseases, 2014)
Malignant rhabdoid tumor was first discovered in the kidney, and rhabdoid tumor of the lung was first reported in 1995. These were included as the variants of large-cell carcinoma, according to the 1999 World Health Organization classification of lung tumors. The rhabdoid tumor of the lung exhibits aggressive biological behavior and has a poor prognosis, and only a few reports of this tumor exist. We report a case of lung carcinoma with a rhabdoid phenotype, initially misdiagnosed as an aspergilloma, in a 48-year-old man who presented with recurrent hemoptysis. The chest computed tomography scans showed a huge consolidative lesion with an air crescent sign in the left upper lung and no contrast-enhancing lesion. An aspergilloma was diagnosed by the radiologist. However, after surgical excision and pathological examination, rhabdoid carcinoma was diagnosed. A surgical resection helps to make it possible to pathologically distinguish a malignancy from an aspergilloma.